Fabric movement and washing performance in a front-loading washer with a built-in pulsator. Issue 21 (November 2019) - Kim, Hyewon; Yun, Changsang; Park, Chung Hee
The objective of this study was to investigate the change of fabric movement by introducing a pulsator in a front-loading washer. To examine the effect of the changed fabric movements on washing performance, detergency, mechanical action, wrinkling, tangling, and tensile strength were also investigated. Three-dimensional fabric movement was analyzed by representing the fabric center in the washer as XYZ coordinate values. Seven indexes of fabric movement were used to analyze the correlation between fabric movement and detergency. On comparing fabric movements using the indexes, the front-loading washer with a built-in pulsator showed more diverse fabric movements than the conventional washer and, in particular, movement in the depth direction of the drum occurred more frequently in the newly developed system. This led to 7.6% higher detergency compared to the conventional one, possibly due to the increased interaction between fabrics. Regression analysis verified that the diversified fabric movements induced by the pulsator in the front-loading washer resulted in the improvement of detergency. The different fabric movements in the newly developed system also affected fabric damage, tangling and wrinkling.